Fuel consumption and gas emissions of an automatic transmission vehicle following simple eco‐driving instructions on urban roads. Issue 7 (1st November 2014) - Larue, Grégoire S.; Malik, Husnain; Rakotonirainy, Andry; Demmel, Sébastien
Abstract : Following eco‐driving instructions can reduce fuel consumption between 5 and 20% on urban roads with manual cars. The majority of Australian cars have an automatic transmission gear box. It is therefore of interest to verify whether current eco‐driving instructions are efficient for such vehicles. In this pilot study, participants ( N = 3) drove an instrumented vehicle (Toyota Camry 2007) with an automatic transmission. Fuel consumption of the participants was compared before and after they received simple eco‐driving instructions. Participants drove the same vehicle on the same urban route under similar traffic conditions. The authors found that participants drove at similar speeds during their baseline and eco‐friendly drives, and reduced the level of their accelerations and decelerations during eco‐driving. Fuel consumption decreased for the complete drive by 7%, but not on the motorway and inclined sections of the study. Gas emissions were estimated with the (Virginia Tech) VT‐micro model, and emissions of the studied pollutants (carbon dioxide (CO2 ), carbon monoxide, oxides of nitrogen and hydrocarbons) were reduced, but no difference was observed for CO2 on the motorway and inclined sections. The difference for the complete lap is 3% for CO2 . The authors have found evidence showing that simple eco‐driving instructions are efficient in the case of automatic transmission in an urban environment, but towards the lowest values of the spectrum of fuel consumption reduction from the different eco‐driving studies.